2017
DOI: 10.1007/s00604-017-2608-2
|View full text |Cite
|
Sign up to set email alerts
|

Boronate-modified hollow molecularly imprinted polymers for selective enrichment of glycosides

Abstract: D-Glucose was used as a dummy template in a strategy to fabricate boronate-based hollow molecularly imprinted polymers (h-MIPs) for the recognition of glycosides. 3-Aminophenylboronic acid (APBA) was selected as the functional monomer to impart glycoside binding capability. A polystyrene core was synthesized via an emulsifier-free emulsion polymerization. It was then be corroded to form a hollow structure where the binding sites on the inner surface can be fully utilized. Adsorption studies indicate that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition, 4-VP as the best monomer on MIP-4VP may help to interact with quercetin specially. Other analogues (luteolin and kaempferol) were also adsorbed through interaction with the cavity of MIPs owing to the steric effect of their similar main structure . After the second step using MIP-AM, only QC was retained, which may be based on the difference of interaction intensities between monomer and template and the orientations for cavity entrance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 4-VP as the best monomer on MIP-4VP may help to interact with quercetin specially. Other analogues (luteolin and kaempferol) were also adsorbed through interaction with the cavity of MIPs owing to the steric effect of their similar main structure . After the second step using MIP-AM, only QC was retained, which may be based on the difference of interaction intensities between monomer and template and the orientations for cavity entrance.…”
Section: Resultsmentioning
confidence: 99%
“…Other analogues (luteolin and kaempferol) were also adsorbed through interaction with the cavity of MIPs owing to the steric effect of their similar main structure. 43 After the second step using MIP-AM, only QC was retained, which may be based on the difference of interaction intensities between monomer and template and the orientations for cavity entrance. When exchanging the extraction order of MIP-4VP and MIP-AM, it was observed that MIP-AM could adsorb quercetin and all analogues at the first extraction step (Figure 6e).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The synthesis method of PS is a reference to our previous method. 28 2.0 g PS was dispersed into 250 mL 2 g L −1 DA solution (Tris–HCl, 20 mM, pH 8.5) and stirred at room temperature for 12 h to obtain PS@PDA. Then, 0.2 g PS@PDA particles, 0.5 mL PEI and 150 mg CDI were dispersed in phosphate buffer solution (PBS) with pH 8.5 and stirred at room temperature for 12 h. The addition of CDI can effectively bind the hydroxyl groups on the PDA surface with amino on PEI.…”
Section: Methodsmentioning
confidence: 99%
“…With this consideration, Hu et al decorated monodisperse carboxylated PS with boronate-affinity MIPs by using D-glucose, 3-Aminophenylboronic acid (APBA) and EGDMA as dummy template, functional monomer and cross-linker, respectively [142]. D-glucose containing a cis-diol group was covalently bonded with boronic acids of APBA in alkaline medium reversibly, and dissociated at acidic pH.…”
Section: Hollow Porous Mipsmentioning
confidence: 99%